Colegiul Tehnic „David Praporgescu” – Turnu Măgurele. Studiu de caz - Deliu, Alexandra (Calitatea Vieții, 2016)
The case study focused on the David Praporgescu Technical College presents some perceptions on the current situation in the school, as well as on the general state of the vocational and technical education system in Romania. Teachers, local entrepreneurs and students were interviewed in the empirical research. The data suggests a discrepancy between the labour market, represented here by the perspectives of the entrepreneurs, and the school. Also, the profiles of students seem to differ in what concerns the clarity of their future plans, function of differences in the chosen specialty at school.